Involvement of Histone Lysine Methylation in p21 Gene Expression in Rat Kidney In Vivo and Rat Mesangial Cells In Vitro under Diabetic Conditions - Xiangjun Li; Chaoyuan Li; Xiaoxia Li; Peihe Cui; Qifeng Li; Qiaoyan Guo; Hongbo Han; Shujun Liu; Guangdong Sun (Journal of Diabetes Research)
Diabetic nephropathy (DN), a common complication associated with type 1 and type 2 diabetes mellitus (DM), characterized by glomerular mesangial expansion, inflammation, accumulation of extracellular matrix (ECM) protein, and hypertrophy, is the major cause of end-stage renal disease (ESRD). Increasing evidence suggested that p21-dependent glomerular and mesangial cell (MC) hypertrophy play key roles in the pathogenesis of DN. Recently, posttranscriptional modifications (PTMs) have uncovered novel molecular mechanisms involved in DN. However, precise regulatory mechanism of histone lysine methylation (HKme) mediating p21 related hypertrophy associated with DN is not clear. We evaluated the roles of HKme and histone methyltransferase (HMT) SET7/9 in p21 gene expression in glomeruli of diabetic rats and in high glucose- (HG-) treated rat mesangial cells (RMCs). p21 gene expression was upregulated in diabetic rats glomeruli; chromatin immunoprecipitation (ChIP) assays showed decreased histone H3-lysine9-dimethylation (H3K9me2) accompanied with enhanced histone H3-lysine4-methylation (H3K4me1/3) and SET7/9 occupancies at the p21 promoter. HG-treated RMCs exhibited increased p21 mRNA, H3K4me level, SET7/9 recruitment, and inverse H3K9me, which were reversed by TGF-β1 antibody. These data uncovered key roles of H3Kme and SET7/9 responsible for p21 gene expression in vivo and in vitro under diabetic conditions and confirmed preventive effect of TGF-β1 antibody on DN.